Framing investment in Mexico: an exploratory content analysis of the news frames of the main Spanish companies in the Mexican press. (16th April 2009) - Muniz, Carlos; Ramirez, Jacobo; Murgan, Andrea; Castillo, Jose Manuel
The mass media can play an important role in the visibility of certain social groups, countries and companies. However, the media also shapes views about the phenomena it addresses, using certain news frames or emotions that are able to play to the role of frames (Nabi, 2003). In order to know what image the Mexican press is offering through its news about Spanish companies that are currently investing in Mexico, an exploratory content analysis was developed. The sample was obtained from the Mexican newspapers that are available in the database LEXIS/NEXIS Academic Universe from January to November of 2007. All of the news items that referenced Spanish investor companies in Mexico were selected and examined using the computerised program Linguistic Inquiry and Word Count (LIWC). This program was used to observe and quantify the emotions, whether negative or positive, that were present in the Mexican press as they informed the public about Spanish companies.